2017
DOI: 10.1038/s41598-017-16129-3
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic silencing of nociceptive primary afferents reduces evoked and ongoing bladder pain

Abstract: Patients with interstitial cystitis/bladder pain syndrome (IC/BPS) suffer from chronic pain that severely affects quality of life. Although the underlying pathophysiology is not well understood, inhibition of bladder sensory afferents temporarily relieves pain. Here, we explored the possibility that optogenetic inhibition of nociceptive sensory afferents could be used to modulate bladder pain. The light-activated inhibitory proton pump Archaerhodopsin (Arch) was expressed under control of the sensory neuron-sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 65 publications
6
59
0
Order By: Relevance
“…Use cases will also need to be organized based on expectations, separating near-term and long-term needs. New computational neuroscience users, use cases, and applications will arise in other specialties as they consider the innervation of other organs ( Barth et al, 2017 ; Samineni et al, 2017 ; Vaseghi et al, 2017 ; Ross et al, 2018 ).…”
Section: Good Practices Contributing To Simulation Credibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Use cases will also need to be organized based on expectations, separating near-term and long-term needs. New computational neuroscience users, use cases, and applications will arise in other specialties as they consider the innervation of other organs ( Barth et al, 2017 ; Samineni et al, 2017 ; Vaseghi et al, 2017 ; Ross et al, 2018 ).…”
Section: Good Practices Contributing To Simulation Credibilitymentioning
confidence: 99%
“…Non-targeted electrostimulation using transcranial electrodes is also being widely used but remains controversial, and lacks precise clinical indications ( Lefaucheur et al, 2014 ; Esmaeilpour et al, 2017 ; Huang et al, 2017 ; Lafon et al, 2017 ; Santos et al, 2017 ). Consideration is also being given to future use of optogenetic stimulation therapies that would offer still greater precision compared to electrical stimulation – targeting not only a particular area but a particular cell type or set of cell types within that area ( Vierling-Claassen et al, 2010 ; Kerr et al, 2014 ; Samineni et al, 2017 ). All such stimulation protocols require identification of suitable, if not necessarily optimal, ranges of parameters, e.g., strength, duration, frequency, waveform, location, iterations, schedule, reference activity, etc.…”
Section: Use Of Modeling In Clinical Domains Of Brain Diseasementioning
confidence: 99%
“…Expression of ChR2 in the CNS has been used to study a number of behaviors, including those related to anxiety, learning, and depression (Huber et al, 2008 ; Covington et al, 2010 ; Tye et al, 2011 ). Recently, optogenetic modulation of bladder smooth muscle was shown to elicit voiding in vivo (Park et al, 2017 ), and our group demonstrated that inhibition of sensory afferent activity via archaerhodopsin, a light-activated proton pump, attenuates pain-related behavior in the context of bladder inflammation (Samineni et al, 2017a ). The present study is an important addition that demonstrates for the first time the effects of direct, selective neuronal activation of distinct bladder afferents on behavioral correlates of bladder sensation and function.…”
Section: Discussionmentioning
confidence: 99%
“…DRGs were sectioned and stained as previously described 38 . Briefly, 6-8 days after HSV viral vector injection, rats were perfused with PBS and 4% PFA as described above.…”
Section: Methodsmentioning
confidence: 99%